The Relationship Between The Implementation of a CCTV-Based Monitoring System and Compliance With Ppe Usage at The Lrt Jakarta Propertindo Velodrome – Manggarai Project Site KSO PT Len Railway System 2024 - Darmawan, Abdul Ghany; Siddiq, Maulana; Baihaqi, Tizar; Iriani, Yani (Institut Teknologi Adhi Tama Surabaya, 2025)
Implementation of occupational safety and health is one part of the workforce protection aspect to achieve optimal work productivity. In connection with the implementation of occupational safety and health, the use of Personal Protective Equipment is an effort to protect or prevent potential dangers or work accidents. To describe the relationship between the implementation of CCTV-based monitoring and compliance with the use of Personal Protective Equipment among Jakarta Propertindo Lintas Velodrome - Manggarai LRT project workers in 2024. This research uses a correlative descriptive quantitative research design with the approach used is a Cross Sectional Study conducted on 30 Technician Employees at the Jakarta Propertindo Lintas Veledrome – Manggarai LRT project. The results in this research i statistical results using chi square obtained a P-Value = 0.019 with a degree of confidence or ɑ of 5% (0.05), because the P-Value is 0.019 ɑ value (0.05) meaning that Ho is rejected so it can be It is concluded that this means Ha is accepted or there is a relationship between the Implementation of a CCTV-Based Monitoring System and Compliance with the Use of PPE at the LRT Jakarta Propertindo Lintas Veledrome - Manggarai KSO Project Location of PT Len Railways Systems.